2014
DOI: 10.1007/s00455-013-9513-6
|View full text |Cite
|
Sign up to set email alerts
|

Speech Pathologist Practice Patterns for Evaluation and Management of Suspected Cricopharyngeal Dysfunction

Abstract: Speech pathologists are often the first professionals to identify signs of a cricopharyngeal (CP) dysfunction and make recommendations for further care. There are many care options for patients with CP dysfunction, but it is unclear how certain interventions are used in practice. A paper-based survey employing two clinical cases involving suspected CP dysfunction (Case 1 with adequate pharyngeal strength and Case 2 with coexisting pharyngeal weakness) were sent to members of American Speech-Language Hearing As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…That is, many providers report trying a wide variety of strategies in most patients (compensations, range of motion, strengthening, among others) and prescribe exercises on a daily, high-intensity schedule. [155][156][157] Given the extreme complexity of swallowing, current exercise regimens, even when performed intensively, appear inadequate to rehabilitate the complex swallowing abnormalities typically seen in patients with moderate or severe dysphagia and are reported to have small to moderate effects. 143 Furthermore, ever growing reimbursement reductions, caps, and the emerging focus on value-based health care threaten (rightfully so) extant practices wherein relatively similar therapies are applied for long treatment periods regardless of etiology or progress.…”
Section: Individualized Therapymentioning
confidence: 99%
“…That is, many providers report trying a wide variety of strategies in most patients (compensations, range of motion, strengthening, among others) and prescribe exercises on a daily, high-intensity schedule. [155][156][157] Given the extreme complexity of swallowing, current exercise regimens, even when performed intensively, appear inadequate to rehabilitate the complex swallowing abnormalities typically seen in patients with moderate or severe dysphagia and are reported to have small to moderate effects. 143 Furthermore, ever growing reimbursement reductions, caps, and the emerging focus on value-based health care threaten (rightfully so) extant practices wherein relatively similar therapies are applied for long treatment periods regardless of etiology or progress.…”
Section: Individualized Therapymentioning
confidence: 99%
“…The dysfunction of the upper esophageal sphincter (UES) can significantly hinder the recovery of patients with dysphagia. [1] Botulinum toxin injection is a widely used procedure for the treatment of UES dysfunction. [2]…”
Section: Introductionmentioning
confidence: 99%
“…Shaker exercise is currently the most commonly recommended swallowing exercise by speech-language pathologists for the treatment of dysphagia and based on different studies done for different patients have different disorders as head and neck cancer, stroke and parkinson disease reported that shaker exercise is effective to reduce intensity of dysphagia and improve swallowing abilities but there is no enough researches or scanty number of researches have been conducted to investigate the effect of shaker exercise on dysphagia among patients with hyperthyroidism (Kraaijenga, et al, 2017) [12], (Park ,Hwang ,Oh &Chang, 2017) [14], (Langmore & Pisegna, 2015) [16], (DeJong, 2016) [1] and (Jones, Knigge & McCulloch, 2014) [17].…”
Section: Introductionmentioning
confidence: 99%